Synthesis, characterization and optimization of cocoa pod husk carbon quantum dots - Nazibudin, Nazatul Akmal (2022)
A quasi zero-dimensional carbon quantum dots were successfully synthesised from cocoa pod husk through an eco-friendly and simple hydrothermal reaction. In addition, different analysis was used to approve synthesise of the cocoa pod husks carbon quantum dots such as x-ray diffraction pattern, high resolution transmission electron microscope, fourier-transform infrared reflection spectroscopy, dynamic light scattering and zeta potential analysis. According to the characterization, the product was amorphous carbon with particle sizes 2.1- 4.1 nm and contain various functional groups including hydroxyl and carbonyl. Besides, the photoluminescence (PL) intensity from cocoa pod husk carbon quantum dots can be modified through the optimization of hydrothermal parameters. The PL analysis showed the product has high photoluminescence intensity under optimized synthesis conditions with a quantum yield of 39.3% compared to non-optimized synthesis conditions (25.38%). Overall, the highest PL intensity of CQDs was successfully obtained by setting the hydrothermal temperature to 200°C for 2 hours, at a pH of 10 and a concentration of 1 mg/mL.